Modeling the Effect of Temperature on Brix Concentration of Tomato Juice During Vacuum Concentration - Pham, Ngoc Hung; Le, Tuan Phuc; Hoang, Quoc Tuan; Cung, Thi To Quynh (JST: Engineering And Technology For Sustainable Development, 2023)
Concentrated tomato is produced typically from tomatoes by the conventional method of concentration. Recently, vacuum-concentration processes have been developed to concentrate with the property of reducing variation by high temperature. The aim of this study is to simulate water evaporation and change of tomato juice concentration during vacuum concentration. Mathematical and simulation models for vacuum condensate system are proposed and implemented. Matlab’s ode45 function is used to solve differential equations and simulate systems. The effect of the concentration and condensate temperature on the Brix concentration of the solution was investigated based on the model. Experiments were carried out with 10kg of tomato juice, the initial Brix concentration was 4, with the concentration temperatures of 60°C and 65°C, resulting in the correlation coefficient R² reaching 0.9624 and 0.9837, respectively. This result shows a high compatibility between simulation and experimental. The simulations accurately represent the kinetics of the concentration process and the change in temperature and Brix of tomato juice products in the concentration chamber.